USING THE INTEGRATE-HTA GUIDANCE: EXPERIENCE FROM CADTH. (16th November 2017) - Bond, Ken; Weeks, Laura
Abstract : Objectives: The aim of this study was to describe an initial exploration by CADTH, Canada's pan-Canadian health technology assessment (HTA) agency, in using the INTEGRATE-HTA guidance in the production of an HTA that examined the use of both in-center and in-home dialysis modalities for the treatment of end-stage kidney disease in adults in Canada. Methods and Results: We outline CADTH's standard HTA production process and context and then describe the experience of the assessment team in using the INTEGRATE-HTA guidance, specifically to help structure and guide the use of a logic model, the identification of implementation issues, and the identification and examination of ethical issues. For each of the aspects, we describe and reflect on how the assessment team used the guidance, challenges that were encountered in its use, and whether and how we might address these challenges when using the INTEGRATE-HTA guidance in the future. Conclusions: INTEGRATE-HTA provided detailed and helpful guidance for truly integrating wide-ranging aspects of HTA. Our agency was challenged by a steep learning curve for assessment team members, tight project timelines, and a misalignment of current HTA processes with those required to implement the guidance. Nevertheless, using the guidance initiated a dialogue about what might be needed to assess complex interventions and the potential process changes that could facilitate conducting more integrated assessments.